ANALYSIS FACTOR THAT AFFECTING PURCHASE INTENTION CONSUMER TO REDEEM ONLINE COUPONS IN STARBUCKS MANADO TOWN SQUARE 3 - Pateh, Yolanda Yunifer; Lapian, S.L.H.V Joyce; Rumokoy, Farlane S. (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2018)
Abstract: Online Coupons present an exciting new opportunity to target consumers with highly customized offers. Research on the factors influencing attitude and behavioral intention of consumers using mobile coupons is scanty. This research is quantitative type of research which uses primary data obtained through questionnaire and uses Confirmatory Factor Analysis (CFA) as the analytical tool. The population of this research is the consumer that redeem online coupons in Starbucks Manado Town Square 3, where the sample size is taken from 100 consumer. In this research, there are 20 variables that defined as factors that affecting purchase intention consumer to redeem online coupons at Starbucks Manado Town Square 3. There are 20 variables included in the analysis, and the results show that 1variable are not eligible at the time of data management and 19 variables correlate with other variable.The three primary objective of this study are to analyze factor that affecting purchase intention consumer to reedem online coupong.The results of the study show that perceived usefulness, product quality, lifestyle, and social factor influence the behavior and intention of consumers to redeem online coupons. Starbucks Manado Town Square 3 shouldmaintain and improve the product quality and online coupon to attracting of customer attention. Keywords: purchase intention, confirmatory factor analysis, online coupons